Pete the cat. Construction destruction - Dean, James, 1957- (New York, NY : Harper Festival, an imprint of HarperCollins Publishers, 2015)
Pete the cat gets construction workers and equipment to build the coolest playground ever.
"Includes over 30 stickers"--Front cover.
Ages 4-8.
Keywords: Cats -- Juvenile fiction; Playgrounds -- Juvenile fiction; Construction equipment -- Juvenile fiction; Construction workers -- Juvenile fiction